Rosmarinic Acid in Aromatic Herbs: A Green Extraction and HPLC Approach - Hadeel S. Abd-Alwahab; Rawaa F. Jawad (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Aromatic herbs from the Lamiaceae family represent valuable sources of rosmarinic acid (RA), a polyphenolic compound with notable antioxidant, anti-inflammatory, antimicrobial, and neuroprotective properties. Specific background: Traditional extraction methods such as Soxhlet and maceration consume excessive solvents and time while potentially degrading thermolabile compounds. Knowledge gap: Despite growing interest in green extraction technologies, limited validated protocols exist for combining ultrasound-assisted extraction (UAE) with high-performance liquid chromatography (HPLC) for efficient RA quantification across multiple aromatic species. Aims: This study developed and validated a sustainable UAE-HPLC method for extracting and quantifying RA from six aromatic herbs: Laurus nobilis, Thymus vulgaris, Salvia rosmarinus, Anethum graveolens, Mentha viridis, and Salvia officinalis. Results: Using ethanol:water (70:30 v/v) at 40 kHz and 250 W, optimal extraction occurred within 2.5-10 minutes, with Thymus vulgaris yielding the highest RA concentration (170,500 µg/mL). HPLC analysis demonstrated excellent linearity (R² > 0.998) and reproducibility. Novelty: This approach significantly reduces solvent consumption and extraction time while maintaining analytical precision. Implications: The validated UAE-HPLC platform provides a robust, environmentally friendly analytical framework for sustainable utilization of RA-rich herbs in nutraceutical and pharmaceutical applications.Highlight : UAE offers a rapid, low-solvent, and environmentally friendly approach for extracting RA. Variation in RA yields reflects differences in plant tissue structure and extraction conditions. HPLC provides reliable quantification, supporting accurate and consistent analysis of RA. Keywords : Rosmarinic Acid, Aromatic Herbs, Ultrasound-assisted Extraction, HPLC, Green Extraction